Comparative VUV Synchrotron Excitation Study of YAG: Eu and YAG: Cr Ceramics - Zhunusbekov, Amangeldy M.; Karipbayev, Zhakyp T.; Tolegenova, Akbota; Kumarbekov, Kuat K.; Nurmoldin, Erik E.; Baizhumanov, Muratbek M.; Kotlov, Aleksei Aleksei; Popov, Anatoli I. (MDPI, 2024)
Using synchrotron radiation, a comparative VUV excitation study of YAG ceramics doped with Eu3+ and Cr3+ ions under VUV excitation (10.5–3.7 eV) at 9 K was conducted in this work. Both ceramics exhibit distinct excitation peaks in the VUV region, indicating high-energy transitions related to the internal electronic levels of the dopants and interband transitions within the YAG matrix. For YAG:Eu, the main excitation peaks at 6–7 eV correspond to transitions within the 4f-shell of Eu3+ and Eu3+-O2− charge transfer states, showing weak dependence on the crystal field and high energy conversion efficiency. In contrast, YAG:Cr shows broad excitation bands due to transitions between levels influenced by strong crystal field interactions, resulting in lower luminescence efficiency. The study highlights the importance of crystal structure and dopant interactions in determining the spectral characteristics of YAG-based ceramics, offering potential for their application in advanced optoelectronic devices. © 2024 by the authors. --//-- This is an open-access article Zhunusbekov, A.M.; Karipbayev, Z.T.; Tolegenova, A.; Kumarbekov, K.K.; Nurmoldin, E.E.; Baizhumanov, M.M.; Kotlov, A.; Popov, A.I. Comparative VUV Synchrotron Excitation Study of YAG: Eu and YAG: Cr Ceramics. Crystals 2024, 14, 897. https://doi.org/10.3390/cryst14100897 published under the CC BY 4.0 licence.
This research was funded by Committee of Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. AP14871114). In addition, Anatoli Popov was supported by Latvian research project lzp-2023/1\u20130453 \u201CPrediction of long-term stability of functional materials under extreme radiation conditions\u201D and Latvian State Research Programme on Nr. VPP-IZM-CERN-2022/1-0001. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; ceramics; europium; VUV excitation; X-ray diffractometry; yttrium luminum garnet